Blindness and visual impairment in southern Malawi - Chirambo, M. C. (1986)
There is a paucity of reliable information on the prevalence and causes of blindness in sub-Saharan Africa, and this produces problems in designing and evaluating blindness prevention programmes. To address this problem and to provide baseline data for the evaluation of such programmes, the government of Malawi, in conjunction with a number of agencies, conducted a population-based prevalence survey of ocular disease in the Lower Shire River Valley in southern Malawi, an area where blindness is common. The prevalence of bilateral blindness found (1.27%) is similar to that in other developing countries and represents a significant public health problem. At least 60% of this blindness is preventable or easily reversible.